Experiência de aprendizagem mediada apoiada por uma plataforma adaptativa: um estudo com crianças em situação de vulnerabilidade social - Felício, Alexandre César (2023)
In this research, an eight-week study was proposed involving children in situations of social vulnerability, with the aim of elucidating the potential contributions that adaptive learning, in conjunction with the parameters of Reuven Feuerstein's Mediated Learning Experience, may offer for the learning of additive structures, following the principles of Gérard Vergnaud's Theory of Conceptual Fields. Data collection was carried out through initial and final written assessments, as well as on the Adaptive Digital Platform, which aimed to develop personalized learning paths for the students. The following specific objectives were outlined for this study: a) to apply the Mediated Learning Experience as an intervention strategy for cognitive and emotional development of the students, b) to use an adaptive supplementary teaching platform, mediating knowledge with the goal of providing personalized intervention based on student performance, c) to conduct a qualitative analysis of the results of mathematical assessments, considering the cognitive aspects presented in the Theory of Conceptual Fields, with an emphasis on problem-solving in the daily lives of the children, d) to conduct an attitudinal analysis of the students according to the parameters of the Mediated Learning Experience. The results presented suggest that mediation conducted through an adaptive platform, along with the role of a mediator in the classroom, can be a valuable tool in improving mathematical learning in children in situations of social vulnerability. We conducted a qualitative analysis through the collection of speech turns and records in the teaching materials, and the results suggests that mathematical thinking for solving problems involving additive structures can be developed and evolve into more complex situations when students encounter structured mediation with an expectation of success, as advocated by Feuerstein. This research also provides significant insights for more inclusive and equitable educational practices